On φ−Quasiconformally Symmetric N(k)−Contact Metric Manifolds: Avik De, Yoshio Matsuyama - Team, Support (Thai Journal of Mathematics, 2018)
The object of the present paper is to study locally and globally φ−quasiconformally symmetric N(k)−metric manifolds. We prove that a globally φ−quasiconformally N(k)−contact metric manifold M2n+1(n ≥ 1) is Sasakian. Some observations for a 3-dimensional locally φ−symmetric N(k)−contact metric manifold are given. We also give an example of a 3-dimensional locally φ−quasiconformally symmetric N(k)−contact metric manifold.